2014
DOI: 10.1186/s12917-014-0303-7
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of (1-(4-hydroxy-phenyl)-3-m-tolyl-propenone chalcone in indomethacin-induced gastric erosive damage in rats

Abstract: BackgroundNon-steroidal anti-inflammatory drugs (NSAIDs) can result in peptic ulcer disease (PUD) which is a common condition worldwide. The aim of this study was to evaluate the antiulcer properties of (1-(4-hydroxy-phenyl)-3-m-tolyl-propenone) (HPTP) chalcone in rats using indomethacin as ulcerogenic agent.ResultsNone of the rats showed symptoms of kidney and liver toxicity during the term of the study. Administration of HPTP had decreased the acidity, increased gastric wall mucus and flattening of gastric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 27 publications
1
26
0
2
Order By: Relevance
“…Thus, these results demonstrate that C. barometz hair extract is a protective agent and prevents alcohol-induced damage to the rat stomach, which is associated with decreased expression of the Bax protein. Similarly, many amendments have been described by many investigators [18, 48]. Animals pre-fed with C. barometz hair extract displayed decreased expression of the Bax protein.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, these results demonstrate that C. barometz hair extract is a protective agent and prevents alcohol-induced damage to the rat stomach, which is associated with decreased expression of the Bax protein. Similarly, many amendments have been described by many investigators [18, 48]. Animals pre-fed with C. barometz hair extract displayed decreased expression of the Bax protein.…”
Section: Discussionmentioning
confidence: 68%
“…Edema and hemorrhagic abrasions in the mucosal layer in the ulcer control group is known as an indicator of ethanol damage. These effects agree with other results reported by several researchers 32,56,5862. In the PAS staining assessment, this study demonstrated that C. barometz extract heightened the content of glycoprotein in the gastric mucosa (the magenta color).…”
Section: Discussionsupporting
confidence: 93%
“…Gastric ulcer is a disease that affects a large number of people in the world.It is corroded in the duodenum or the lining of the stomach happening on a site where the mucosal epithelium is presented to pepsin and acid and it is instigated by numerous factors, including smoking, stress, alcohol consumption, nutritional deficiencies and regular ingestion of non-steroidal anti-inflammatory drugs (NSAIDs) (Belaiche et al, 2002).Gastric ulcers related to the usage of NSAIDs stay one of the major clinical issues everywhere throughout the world (Dhiyaaldeen et al,2014). Tulassay and Herszényi (2010) detailed that the pathophysiology of gastric ulcers depends on the imbalance between defensive factors and the aggressiveness of the gastric mucosa.…”
Section: Introductionmentioning
confidence: 99%